Chemical analysis of fenugreek plant ( Trigonlla foenum-graecum L. ) Sprayed with nitrogen and zinc (Journal of the College of Basic Education, 2023)
A vital experiment was carried out during the winter season 2010-2011 in the greenhouse belonging to theDepartment of Life Sciences/College of Education for Pure Sciences/University of Baghdad, with the aim of determining plant responseFenugreek for some paper transactions with mineral elements (nitrogen and zinc) and its effect onThe content of some elements (M, K, E©, P1) and the concentration of carbohydrates. Experiment includedA study of the effect of three concentrations of each of the nitrogen fertilizer is 0,1000,2000 mg/lZinc sulfate fertilizer is 50.25.0 mg/L within the global experimental system according to the designRandomized complete sections with three replications. The studied data were analyzed statisticallyFor the above design, the averages of the treatments were compared based on the least significant difference testat a significant level of 5%. The results of the study showed the following: The addition of foliar fertilizernitrogenous lead to a significant increase, as the concentration gave 2000 mg / liter values for the contentThe above elements amounted to 21.55, 48.03, 46.86, 10.73, 54.54 mg / g, respectively, and a concentration ofCarbohydrates% 9.28, and the addition of foliar fertilizer with zinc sulfate had a significant effect.